Copper(ii) salen-based complexes as potential anticancer agents. (14th June 2022) - Mohan, Nithya; Vidhya, C. V.; Suni, V.; Mohamed Ameer, Jimna; Kasoju, Naresh; Mohanan, P. V.; Sreejith, S. S.; Prathapachandra Kurup, M. R.
Abstract : The systematic design and synthesis of four Cu(ii ) salen compounds and their potential as excellent anticancer agents is discussed using biological studies. Abstract : In this work, we have systematically designed and synthesized four Cu(ii ) salen compounds (1 –4 ), which have been characterized using various spectroscopic and analytical techniques. Single-crystal XRD studies were carried out on three of the compounds (1, 2 and 4 ), which revealed that all of them have a water molecule encapsulated/pseudo-encapsulated in the N2 O4 cavity. The binding affinity of the complexes with calf thymus DNA (CT-DNA) was explored using UV-visible and fluorescence techniques. The compounds exhibit excellent DNA binding and cleavage activities. The binding mechanism was probed by molecular docking studies. These results display high binding-constant values owing to the intercalative type of binding. In addition, the binding affinity of the compounds with proteins was also studied via an in silico molecular-docking method using human serum albumin as the receptor. The in vitro cytotoxic effect of the complexes was evaluated in the HeLa cell line, derived from cervical cancer cells. The cleavage of DNA strands was investigated using gel electrophoresis. All of the tested compounds show a high binding-constant value with both DNA and protein and exhibit cytotoxic effects towards cancerous cells. The observed toxicity of these compounds towards a normal cell line could be minimized via interaction of the metal centre with the detoxifier glutathione, and detoxification studies were also conducted. The synthesized compounds were found to be potential candidates for the pharmaceutical industry. Considering the results and compared with existing reports, we propose a promising candidate (compound 4 ) for the development of efficient therapeutic drugs.